Differences among regions in environmental predictors of primate community similarity affect conclusions about community assembly. (25th January 2019) - Beaudrot, Lydia; Marshall, Andrew J.
Abstract: Understanding why ecological communities contain the species they do is a long-standing question in ecology. Two common mechanisms that affect the species found within communities are dispersal limitation and environmental filtering. Correctly identifying the relative influences of these mechanisms has important consequences for our understanding of community assembly. Here variable selection was used to identify the environmental variables that best predict tropical forest primate community similarity in four biogeographic regions: the Neotropics, Afrotropics, Madagascar and the island of Borneo in South-East Asia. The environmental variables included net primary productivity and altitude, as well as multiple temperature, precipitation and topsoil variables. Using the best environmental variables in each region, Mantel and partial Mantel tests were used to reanalyse data from a previously published study. The proportion of variance explained increased for each region. Despite increases, much of the variation remained unexplained for all regions (R 2 : Africa = 0.45, South America = 0.16, Madagascar = 0.28, Borneo = 0.10), likely due to different evolutionary and biogeographic histories within each region. Nonetheless, substantial variation among regions in the environmental variables that best predicted primate community similarity were documented. For example, none of the 14 environmental variables was included for all four regions, yet each variable was included for at least one region. Contrary to prior results, environmental filtering was an important assembly mechanism for primate communities in tropical forests worldwide. Geographic distance more strongly predicted African and South American communities whereas environmental distance more strongly predicted Malagasy and Bornean communities. These results suggest that dispersal limitation structures primate communities more strongly than environmental filtering in Africa and in South America whereas environmental filtering structures primate communities more strongly than dispersal limitation in Madagascar and Borneo. For communities defined by genera, environmental distance more strongly predicted primate communities than geographic distance in all four regions, which suggests that environmental filtering is a more influential assembly mechanism at the genus level. Therefore, a more nuanced consideration of environmental variables affects conclusions about the influences of environmental filtering and dispersal limitation on primate community structure.